2020
DOI: 10.26434/chemrxiv.12725465.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supercomputer-Based Ensemble Docking Drug Discovery Pipeline with Application to Covid-19

Abstract: We present a supercomputer-driven pipeline for <i>in-silico</i> drug discovery using enhanced sampling molecular dynamics (MD) and ensemble docking. We also describe preliminary results obtained for 23 systems involving eight protein targets of the proteome of SARS CoV-2. THe MD performed is temperature replica-exchange enhanced sampling, making use of the massively parallel supercomputing on the SUMMIT supercomputer at Oak Ridge National Laboratory, with which more than 1ms of enhanced sampling MD… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 126 publications
0
46
0
Order By: Relevance
“…Probabilities of assignment to each conformational state can be used as reaction coordinates. We are presently applying the method to classify chemical compound space using binary MACCS fingerprints [21], and to characterize conformational space of SARS-CoV-2 proteins simulated using replica exchange molecular dynamics [22]. Now that the principle has been demonstrated, more informative classification schemes can be devised.…”
Section: Discussionmentioning
confidence: 99%
“…Probabilities of assignment to each conformational state can be used as reaction coordinates. We are presently applying the method to classify chemical compound space using binary MACCS fingerprints [21], and to characterize conformational space of SARS-CoV-2 proteins simulated using replica exchange molecular dynamics [22]. Now that the principle has been demonstrated, more informative classification schemes can be devised.…”
Section: Discussionmentioning
confidence: 99%
“…For example, OpenEye GigaDocking 44 was used to dock the Enamine REAL database into the purine nucleoside phosphorylase and heat shock protein 90 targets in <1 d using 27,000 and 45,000 Amazon Web Services (AWS) cloud CPUs, respectively. The popular Autodock program has been parallelized for Compute Unified Device Architecture (CUDA) 45 and deployed on the Summit supercomputer (comprising >27,000 GPUs) to dock the same library into the SARS-CoV-2 Mpro active site in ~1 d 5 .…”
Section: Comparison With Alternative Methodsmentioning
confidence: 99%
“…On the other hand, the emergence of ultra-large libraries has highlighted significant limitations of conventional docking approaches that typically operate on the scale of millions of molecules. With chemical libraries comprising 100 billion molecules on the horizon 4 , it will soon become impossible to deploy conventional docking at its full potential, and so far, only a handful of billion-sized docking campaigns have been conducted on elite supercomputing facilities 2,5 .…”
Section: Introductionmentioning
confidence: 99%
“…In one of the largest docking studies reported to date, 138 million and 99 million compounds from the Enamine REAL library were docked against the D 4 receptor and AmpC, respectively [55]; this was enabled by a fast computational pipeline requiring only one second per library compound. More recent studies have since screened over one billion enumerated molecules from the same database [65,66]. As several make-on-demand libraries exceed this scale by multiple orders of magnitude, we argue that such exhaustive screening techniques are not a viable long-term approach even for inexpensive evaluations like docking.…”
Section: Exploring Finite Chemical Spacesmentioning
confidence: 98%